Noninvasive Measurement of Carbon Dioxide during One-Lung Ventilation with Low Tidal Volume for Two Hours: End-Tidal versus Transcutaneous Techniques - Zhang, Hong (PLoS One, 2015)
BACKGROUND: There may be significant difference between measurement of end-tidal carbon dioxide partial pressure (PetCO(2)) and arterial carbon dioxide partial pressure (PaCO(2)) during one-lung ventilation with low tidal volume for thoracic surgeries. Transcutaneous carbon dioxide partial pressure (PtcCO(2)) monitoring can be used continuously to evaluate PaCO(2) in a noninvasive fashion. In this study, we compared the accuracy between PetCO(2) and PtcCO(2) in predicting PaCO(2) during prolonged one-lung ventilation with low tidal volume for thoracic surgeries. METHODS: Eighteen adult patients who underwent thoracic surgeries with one-lung ventilation longer than two hours were included in this study. Their PetCO(2), PtcCO(2), and PaCO(2) values were collected at five time points before and during one-lung ventilation. Agreement among measures was evaluated by Bland-Altman analysis. RESULTS: Ninety sample sets were obtained. The bias and precision when PtcCO(2) and PaCO(2) were compared were 4.1 ± 6.5 mmHg during two-lung ventilation and 2.9 ± 6.1 mmHg during one-lung ventilation. Those when PetCO(2) and PaCO(2) were compared were -11.8 ± 6.4 mmHg during two-lung ventilation and -11.8 ± 4.9 mmHg during one-lung ventilation. The differences between PtcCO(2) and PaCO(2) were significantly lower than those between PetCO(2) and PaCO(2) at all five time-points (p < 0.05). CONCLUSIONS: PtcCO(2) monitoring was more accurate for predicting PaCO(2) levels during prolonged one-lung ventilation with low tidal volume for patients undergoing thoracic surgeries.